A Cross Sectional Survey to Determine the Effect of Consuming Regular Breakfast on BMI in Medical Students of Jinnah Medical and Dental College (Medical Forum Monthly, 2024)
Objective: The objective of this cross sectional survey was to determine the effect of consuming regular breakfast on BMI in medical students of Jinnah Medical and Dental College.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted among the medical students of Jinnah Medical and Dental College, Karachi, from April 2014 to August 2014.Materials and methods: The sample comprised of all the students of first to fourth year MBBS students. 374 students actually became the part of our study. The data was collected using a pre tested and pre coded questionnaire. The data was analyzed by using SPSS version 20.0Results: Our study reveals that 43% (n=161) were the regular breakfast consumers compared to 57% (n=213) who were irregular breakfast eaters. From this regular breakfast consumers 63.2% (n=102) had normal BMI and 36.8% (n=59) had deviant BMI. From this deviant BMI group 64 %(n=38) of the students were underweight and 36 %( n=21) were obese.Conclusion: The findings of our study support earlier research which suggests that regular breakfast consumption helps to keep our BMI within normal range.